History Learning As A Basis Of Character Education: Comparative Analysis According to Perspectives JW Foerster, Thomas Lickona and Erich Fromm - Ahmad Kosasih (Sosio e-Kons, 2021)
Character education is a learning model that aims to introduce character values to students, which include the value of love for God and His creation, responsibility, honesty, fairness, mutual respect and courtesy, caring, cooperation, confidence, creative and innovative, hard work, never give up, tolerance, love peace, and love unity. Character education is basically designed and implemented to help students understand the character values in humans individually (cognitive, affective, and psychomotor), or even in the context of their socio-cultural interactions (family, school, community and nation). This study attempts to describe the theoretical basis of character education as a basis for learning, especially in the learning of the Social Studies field of History in Elementary Schools, by referring to the perspective of JW Foster, Thomas J. Lickona, and Erich Fromm. With the results of this study, at least the basic similarities and differences can be described in placing the context of character education as the basis for character education development in accordance with the principles of education in Indonesia which are knowledgeable and ethical.